Physiological and lipidomic response of exogenous choline chloride alleviating salt stress injury in Kentucky bluegrass (Poa pratensis) - Zuo, Zhi-Fang; Li, Yan; Mi, Xin-Feng; Li, Yong-Long; Zhai, Chen-Yuan; Yang, Guo-Feng; Wang, Zeng-Yu; Zhang, Kun (Frontiers in Plant Science, 2023)
Choline participates in plant stress tolerance through glycine betaine (GB) and phospholipid metabolism. As a salt-sensitive turfgrass species, Kentucky bluegrass (Poa pratensis) is the main turfgrass species in cool-season areas. To improve salinity tolerance and investigate the effects of choline on the physiological and lipidomic responses of turfgrass plants under salinity stress conditions, exogenous choline chloride was applied to Kentucky bluegrass exposed to salt stress. From physiological indicators, exogenous choline chloride could alleviate salt stress injury in Kentucky bluegrass. Lipid analysis showed that exogenous choline chloride under salt-stress conditions remodeled the content of phospholipids, glycolipids, and lysophospholipids. Monogalactosyl diacylglycerol, digalactosyl diacylglycerol, phosphatidylcholine, phosphatidylethanolamine, phosphatidylserine, and lysophosphatidylcholine content were increased and phosphatidic acid content were decreased in plants after exogenous choline chloride under salt treatment. Plant leaf choline content increased, but GB was not detected in exogenous choline chloride treatment plants under nonstress or salt-stress conditions. GB synthesis pathway related genes showed no clear change to choline chloride treatment, whereas cytidyldiphosphate-choline (CDP-choline) pathway genes were upregulated by choline chloride treatment. These results reveal that lipid remodeling through choline metabolism plays an important role in the salt tolerance mechanism of Kentucky bluegrass. Furthermore, the lipids selected in this study could serve as biomarkers for further improvement of salt-sensitive grass species.